Pannexin1: Role as a Sensor to Injury Is Attenuated in Pretype 2 Corneal Diabetic Epithelium - Garrett Rhodes; Kristen L. Segars; Yoonjoo K. Lee; Audrey E. K. Hutcheon; Celeste B. Rich; Vickery Trinkaus-Randall (Analytical Cellular Pathology)
Epithelial wound healing is essential to repair the corneal barrier function after injury and requires coordinated epithelial sheet movement over the wounded region. The presence and role of pannexin1 on multilayered epithelial sheet migration was examined in unwounded and wounded corneal epithelium from C57BL/6J (B6) control and diet-induced obese (DiO) mice, a pretype 2 diabetic model. We hypothesize that pannexin1 is dysregulated, and the interaction of two ion-channel proteins (P2X7 and pannexin1) is altered in pretype 2 diabetic tissue. Pannexin1 was found to be present along cell borders in unwounded tissue, and no significant difference was observed between DiO and B6 control. However, an epithelial debridement induced a striking difference in pannexin1 localization. The B6 control epithelium displayed intense staining near the leading edge, which is the region where calcium mobilization was detected, whereas the staining in the DiO corneal epithelium was diffuse and lacked distinct gradation in intensity back from the leading edge. Cells distal to the wound in the DiO tissue were irregular in shape, and the morphology was similar to that of epithelium inhibited with 10Panx, a pannexin1 inhibitor. Pannexin1 inhibition reduced mobilization of calcium between cells near the leading edge, and MATLAB scripts revealed a reduction in cell-cell communication that was also detected in cultured cells. Proximity ligation was performed to determine if P2X7 and pannexin1 interaction was a necessary component of motility and communication. While there was no significant difference in the interaction in unwounded DiO and B6 control corneal epithelium, there was significantly less interaction in the wounded DiO corneas both near the wound and back from the edge. The results demonstrate that pannexin1 contributes to the healing response, and P2X7 and pannexin1 coordination may be a required component of cell-cell communication and an underlying reason for the lack of pathologic tissue migration.